Terrorist Activities, Investor Sentiment, and Stock Returns: Evidence from Pakistan - Ali, Hashmat; Menon, Zulfiqar Ali; Khan, Ajab; Khan, Muhammad Muddassar; Ali, Imad; Baz, Khan; Arif, Muhammad; Hussain, Manzoor; Jalal, Waqar (International Journal of Economics and Financial Issues, 2020)
Motivated by the previous literature on investor sentiment and assuming that terrorist activities affect investor mood, this study attempts to address the psychological impact of terrorism for investors in Pakistan stock market. Apart from a direct economic loss, major terrorist incidents create/exacerbate uncertainty and fear in the market. The investors are likely to over-respond to such incidents and once the dust settles the market tend to recover. The analysis of cumulative abnormal returns in the aftermaths of terrorist incidents and the volume analysis provide strong evidence that the terrorist incidents adversely affect investors' sentiments and confidence in the market as manifested through relatively feeble trading volumes. Keywords: Sentiment, Terrorism, Stock Market, Pakistan JEL Classifications: C33, E44, G15 DOI: https://doi.org/10.32479/ijefi.9591